Organising health visiting services in the UK: Frontline perspectives. (2nd February 2021) - Whittaker, Karen; Appleton, Jane V; Peckover, Sue; Adams, Cheryll
Abstract : The organisation of health visitor work is an important part of service design, which can have an impact on when and where services are provided and who gains access. This article reports a 2018 survey of UK health visitors conducted to provide an overview of the range of ways in which health visitor cases and workloads are organised. The 584 respondents confirmed the operation of three broad types of health visitor service delivery models; namely, the individual case, the corporate case and the combination model. Themes that emerged from practitioners' experiences of working with the different models reflected concerns about continuity and staffing, accommodating different needs and different services in different places. Overall, the data indicated a lack of consistency in health visitor service across the UK. The advantages and disadvantages of each workload model are detailed and considered with respect to markers of a quality service, including achieving relationships with clients and sufficient communication within and across teams.